Autoantibodies against the chromosomal passenger protein INCENP found in a patient with Graham Little-Piccardi-Lassueur syndrome - Rodríguez-Bayona, Beatriz (BioMed Central, 2007)
BACKGROUND: Graham Little – Piccardi – Lassueur (GLPL) syndrome is a rare dermatosis characterized by scarring alopecia, loss of pubic and axillary hair, and progressive development of variously located follicular papules. We report a first case ever of an autoimmune response in a patient suffering from GLPL syndrome. METHODS: Immunofluorescence and immunoblot analysis were used in a variety of cell cultures including human, monkey, hamster, mouse and bovine cells to analyze the presence of autoantibodies in a GLPL patient. RESULTS: The autoimmune serum showed a pattern of centromere and spindle microtubule staining resembling that of the chromosomal passenger protein complex. By using a complex of proteins expressed in baculovirus, immunoblot analysis demonstrated that the INCENP protein is a major autoantigen in this patient with GLPL syndrome. CONCLUSION: An autoimmune response in GLPL syndrome is reported against the INCENP centromere protein. The occasional development of autoimmunity in GLPL patients could serve as a test in continuing efforts to detect this disease and for a more directed therapy based on the autoantigen response.